INTERNALISASI NILAI - NILAI KETELADANAN TOKOH ISLAM RADEN PATAH PADA PEMBELAJARAN PAI SISWA KELAS VIII (Studi kasusdi MTs. Al-Hamid Malang) - Mas Habib Amrulloh; Azhar Haq; Syamsu Madyan (VICRATINA, 2020)
This article is in the form of an idea with the title "Internalization of the Exemplary Value of Islamic leader Raden Patah towards PAI learning, starting with findings in the field, historical learning is cognitive-oriented, lacking attention to the meaning of didactic and affective. In this article, we want to find a number of solutions to change views in the preparation and development of historical material. descriptive-analytic qualitative approach applied in this paper. Through character development students can actually be effective with historical material. Character education in historical material can be done through the exemplary Islamic leaders. The figures in the history of the archipelago of Islam are the first figures of the spread of Islam in Indonesia, so that it can be a good role model for students to apply in learning. As for the value of attitudes taken include: (1) Raden broken exemplary attitude toward tolerance, (2) Raden broken attitude towards harmony, then (3) Raden Patah exemplary attitude toward obedience to parents and teachers. Therefore, to develop student character can be done through inspiration from Islamic leaders through some examples which can be taken from historical figures to be applied in learning.